Missing Pieces in Realizing Unity and Coherence in The Jakarta Post News Articles - Natasa Venanda; Nur Hidayat; Faiza Hawa (English Language Education Department, Universitas Majalengka, 2025)
Abstract: This research examines the missing elements in realizing unity and coherence in The Jakarta Post news articles. Five news articles issued in first week of November 2024 were analyzed qualitatively to get the description whether unity and coherence realized in the news articles or not. The results show that four news articles have strong element unity realization, however those news articles lack in realizing coherence because of missing elements like spelling, punctuation, and capitalization. In contrast, one news article is coherent but not unified due to the loss of main idea. Four news articles have one main idea, supporting sentences without conclusion. One news article has two main ideas, supporting sentences without conclusion. The inexistence of conclusion in the writing does not impactful in realizing unity of the articles as long as the supporting sentences develop the main ideas completely (Oshima & Hogue, 2006). Five news articles applied key nouns repetitively, conjunctions, and logical sequence which flowed smoothly between one to another sentences. Nevertheless, four news articles have missing elements in spelling, capitalization, and punctuation. In conclusion, although each news article has missing pieces in realizing one of the elements of unity and coherence, The Jakarta Post news articles still can be a real-world context model of writing which contributes to the higher learning which expose and guide the readers how to write paragraphs well.